Review paperThe evolution of computerized treatment planning for brachytherapy: American contributions - Aronowitz, Jesse N.; Rivard, Mark J. (Journal of Contemporary Brachytherapy, 2014)
Purpose : To outline the evolution of computerized brachytherapy treatment planning in the United States through a review of technological developments and clinical practice refinements. Material and methods: A literature review was performed and interviews were conducted with six participants in the development of computerized treatment planning for brachytherapy. Results: Computerized brachytherapy treatment planning software was initially developed in the Physics Departments of New York’s Memorial Hospital (by Nelson, Meurk and Balter), and Houston’s M. D. Anderson Hospital (by Stovall and Shalek). These public-domain programs could be used by institutions with adequate computational resources; other clinics had access to them via Memorial’s and Anderson’s teletype-based computational services. Commercial brachytherapy treatment planning programs designed to run on smaller computers (Prowess, ROCS, MMS), were developed in the late 1980s and early 1990s. These systems brought interactive dosimetry into the clinic and surgical theatre. Conclusions : Brachytherapy treatment planning has evolved from systems of rigid implant rules to individualized pre- and intra-operative treatment plans, and post-operative dosimetric assessments. Brachytherapy dose distributions were initially calculated on public domain programs on large regionally located computers. With the progression of computer miniaturization and increase in processor speeds, proprietary software was commercially developed for microcomputers that offered increased functionality and integration with clinical practice.